Simple and sensitive LC-MS/MS-based assay for the quantification of dimemorfan in human plasma for use in a pharmacokinetic study - Tan, Hongyi; Peng, Jinfu; Pei, Qi; Yang, Liu; Chen, Jun; Guo, Chengxian; Hua, Ye; Yuan, Hong; Yang, Guoping (Biomedical chromatography, 2015)
Dimemorfan phosphate has been widely used for 40 years throughout the world for the treatment of coughs. This is the first report on the use of an LC‐MS/MS‐based assay for the determination of dimemorfan in human plasma using estazolam as an internal standard after one‐step protein precipitation with acetonitrile. Chromatographic separation was achieved on a Phenomenex Luna C18 column (3 µm, 50 × 2.0 mm) using a fast gradient method, which involves water and methanol as the mobile phase (both containing 0.1% formic acid). Dimemorfan and estazolam were detected with proton adducts at m/z values of 255.8 → 155.1 and 295.0 → 267.0, respectively, in the selected reaction monitoring positive mode. The linear dynamic range of the assay was 0.04–5.00 ng/mL. The chromatographic run time for each plasma sample was <5 min. The method was proven to be accurate, precise, and repeatable. Finally, the developed method was successfully applied for the determination of dimemorfan in a pharmacokinetic study using healthy Chinese subjects. Copyright © 2014 John Wiley & Sons, Ltd.